Doing a literature review in health and social care a practical guide - Aveyard, Helen (Maidenhead, Berkshire, Eng. McGrawHill/Open University Press, 2010)
This step-by-step guide simplifies the process of reviewing published literature, provides a guide to searching, appraising and comparing literature, and offers practical tips on writing up.
Why do a literature review in health and social care -- How do I develop a research question -- What literature will be relevant to my literature review -- How do I search for literature -- How do I critically appraise the literature -- How do I synthesize my findings -- How do I discuss my findings and make recommendations -- How do I present my literature review? And other key questions -- Commonly asked questions.
Keywords: Research -- Methods; Writing; Medicine; Research Design; Review literature as topic; Medical care -- Research -- Methodology; Social service -- Research -- Methodology; Report writing